chi-miR-324-3p Regulates Goat Granulosa Cell Proliferation by Targeting DENND1A - Liu, Yufang; Chen, Yulin; Zhou, Zuyang; He, Xiaoyun; Tao, Lin; Jiang, Yanting; Lan, Rong; Hong, Qionghua; Chu, Mingxing (Frontiers in Veterinary Science, 2021)
Granulosa cell (GC) proliferation provides essential conditions for ovulation in ani-mals. A previous study showed that DENND1A plays a significant role in polycystic ovary syndrome. However, the modulation of DENND1A in GCs remains unclear. Our previous integrated analysis of miRNA-mRNA revealed that the 3’ ’-untranslated region of DENND1A could be a target of chi-miR-324-3p. In this study, we used quantitative- reverse transcription- polymerase chain reaction (RT-qPCR) to investi-gate DENND1A expression in ovarian tissues of high- and low- yielding goats. Fur-ther, dual-fluorescent reporter vector experiments, Cell Counting Kit-8 (CCK-8) as-say, and RT-qPCR were used to elucidate the regulatory pathway of chi-miR-324-3p-DENND1A in GCs. The results revealed an opposite tendency between the expres-sions of chi-miR-324-3p and DENND1A in the ovaries of high- and low-yielding goats. The CCK-8 assay indicated that chi-miR-324-3p overexpression significantly suppressed GC proliferation, whereas chi-miR-324-3p inhibition promoted GC pro-liferation. In addition, the expressions of GC proliferation markers LHR, Cylin D2, and CDK4 showed the same tendency. The dual-fluorescent reporter assay revealed that chi-miR-324-3p directly targeted DENND1A, and the RT-qPCR results revealed that DENND1A expression was inhibited by chi-miR-324-3p. In summary, chi-miR-324-3p inhibited the proliferation of GCs by targeting DENND1A.